2016
DOI: 10.1038/gim.2015.217
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnosis of glycogen storage disease and disorders with overlapping clinical symptoms by massive parallel sequencing

Abstract: Purpose: Glycogen storage disease (GSD) is an umbrella term for a group of genetic disorders that involve the abnormal metabolism of glycogen; to date, 23 types of GSD have been identified. The nonspecific clinical presentation of GSD and the lack of specific biomarkers mean that Sanger sequencing is now widely relied on for making a diagnosis. However, this gene-by-gene sequencing technique is both laborious and costly, which is a consequence of the number of genes to be sequenced and the large size of some g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 19 publications
(24 reference statements)
1
37
0
Order By: Relevance
“…Many studies (32)(33)(34)(35)(36)(37) identified mutations in genes responsible for LOPD and other metabolic myopathies in patients with a wide range of phenotypes (Table 2). At the same time, a well-known homozygous mutation in ANO5, responsible for a wide spectrum of disorders described under the umbrella term "anoctaminopathy" (38,39), was identified in a patient suspected of having glycogen storage disease because of the presence of glycogen containing vacuoles on muscle biopsy (40).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies (32)(33)(34)(35)(36)(37) identified mutations in genes responsible for LOPD and other metabolic myopathies in patients with a wide range of phenotypes (Table 2). At the same time, a well-known homozygous mutation in ANO5, responsible for a wide spectrum of disorders described under the umbrella term "anoctaminopathy" (38,39), was identified in a patient suspected of having glycogen storage disease because of the presence of glycogen containing vacuoles on muscle biopsy (40).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a large cohort from Saudi‐Arabia sequenced by custom large gene panels was reported to yield 43% of clinical diagnostic findings in a consanguineous population . In addition, large gene panels have been used in disease‐specific study groups . To our knowledge, however, there have been no published reports on the clinical utility of large gene panel sequencing in a large unselected diagnostic cohort from an outbred population.…”
Section: Introductionmentioning
confidence: 99%
“…11 In addition, large gene panels have been used in disease-specific study groups. 12,13 To our knowledge, however, there have been no published reports on the clinical utility of large gene panel sequencing in a large unselected diagnostic cohort from an outbred population. In this report, we aim to share our experience from the first 1.5 years of large gene panel sequencing in a clinical setting, which involved 501 cases.…”
Section: Introductionmentioning
confidence: 99%
“…With both panels, the libraries generated were sequenced using 150 bp paired-end reads employing the Illumina MiSeq or Nextseq500 NGS platforms. SNVs was annotated and subsequently filtered as previously described [ 26 ]. Variants were always confirmed by conventional Sanger sequencing employing both patient genomic DNA and that of their parents if available.…”
Section: Methodsmentioning
confidence: 99%